Were it physically safe, reproductive human cloning may be acceptable - Devolder, K (Wiley-Blackwell, 2013)
In this paper, I discuss a range of concerns expressed about human reproductive cloning, and argue that most of these concerns are unjustified, or at least more controversial than is generally assumed. Moreover, to the extent that some concerns are justified, the question remains whether they can support a conclusive argument against human reproductive cloning. This will depend on how strong reasons for reproductive cloning are. I conclude that if cloning were physically safe, it may be permissible for people to use it as a means of reproduction.